2023
DOI: 10.1002/cpt.2989
|View full text |Cite
|
Sign up to set email alerts
|

Digital Therapeutics as a New Therapeutic Modality: A Review from the Perspective of Clinical Pharmacology

Benjamin Ribba,
Richard Peck,
Lucy Hutchinson
et al.

Abstract: The promise of transforming digital technologies into treatments is what drives the development of digital therapeutics (DTx), generally known as software applications embedded within accessible technologies—such as smartphones—to treat, manage, or prevent a pathological condition. Whereas DTx solutions that successfully demonstrate effectiveness and safety could drastically improve the life of patients in multiple therapeutic areas, there is a general consensus that generating therapeutic evidence for DTx pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Even engagement itself may require mechanistic research as it has proven to be a challenging construct to improve upon. For example, a recent review of digital therapeutics suggested that the field could benefit from the application of clinical pharmacology principles from the drug development field, such as a stepwise and progressive focus on engagement and adherence, proxy of effects, and clinical end points [ 104 ]. This would need funders to launch specific calls for this type of research (as this is intricate and costly) and is explored further in theme 3 in the following section.…”
Section: Resultsmentioning
confidence: 99%
“…Even engagement itself may require mechanistic research as it has proven to be a challenging construct to improve upon. For example, a recent review of digital therapeutics suggested that the field could benefit from the application of clinical pharmacology principles from the drug development field, such as a stepwise and progressive focus on engagement and adherence, proxy of effects, and clinical end points [ 104 ]. This would need funders to launch specific calls for this type of research (as this is intricate and costly) and is explored further in theme 3 in the following section.…”
Section: Resultsmentioning
confidence: 99%
“…In WHO's Comprehensive Mental Health Action Plan 2013–2030 it is planned to boost mental health promotion and prevention strategies, as well as to strengthen the mental health information systems as well as digital opportunities in mental disorders [ 1 ]. Indeed, digital psychiatry may offer different prevention, management, and treatment interventions for a broad spectrum of physical, mental, and behavioural conditions [ 2 ]. In the field of mental health, many digitally-delivered interventions have been developed for delivering effective and feasible treatments for several mental conditions, including mood disorders [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, digital psychiatry may offer different prevention, management, and treatment interventions for a broad spectrum of physical, mental, and behavioural conditions [ 2 ]. In the field of mental health, many digitally-delivered interventions have been developed for delivering effective and feasible treatments for several mental conditions, including mood disorders [ 2 ]. Indeed, few digital mental health interventions are effectively supported by scientific and clinical evidence, such as the digital therapeutics (DTx).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribba et al 26 show how in silico approaches themselves have become novel modalities in their own right. In their review, they make the case that fundamental clinical pharmacology principles can benefit the development of digital therapeutics (generally known as software applications embedded within accessible technologies-such as smartphones-to treat, manage, or prevent a pathological condition) in three areas: characterization of the mechanism of action, optimization of the intervention, and dosing.…”
mentioning
confidence: 99%